2004
DOI: 10.1002/elps.200305694
|View full text |Cite
|
Sign up to set email alerts
|

Capillary zone electrophoresis for determination of carbohydrate‐deficient transferrin in human serum

Abstract: Carbohydrate-deficient transferrin (CDT) is the most specific marker for diagnosis of chronic excessive alcohol consumption and includes the serum transferrin (Tf) isoforms with two or less sialic acid residues (di-, mono-, and asialo-Tf). To monitor serum CDT, we developed a capillary zone electrophoresis (CZE) method based on the dynamic capillary coating with diethylenetriamine (DETA). The separation was performed in a bare fused-silica capillary (50 microm ID, 57 cm in length), applying a voltage of 25 kV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…A further dynamic coating was recently proposed by Fermo et al [30]. The reported method was similar to the previous CZE methods (separation in 100 mM borate buffer pH 8.4), but for the use of 3 mM diethylenetriamine as buffer additive.…”
Section: Electrophoretic Methodsmentioning
confidence: 79%
“…A further dynamic coating was recently proposed by Fermo et al [30]. The reported method was similar to the previous CZE methods (separation in 100 mM borate buffer pH 8.4), but for the use of 3 mM diethylenetriamine as buffer additive.…”
Section: Electrophoretic Methodsmentioning
confidence: 79%
“…Besides aliphatic polyamines [41][42][43], alkylaminosilyl monomers [44] and oligoamines such as triethylenetetramine and diethylenetriamine [45,46] have also been used to reduce the surface charge and so EOF.…”
Section: Dynamic Wall Coatingmentioning
confidence: 99%
“…Carbohydrate-deficient transferrin, which is the most specific marker for the diagnosis of chronic alcoholism, was analyzed in serum by CZE [46,204]. Asialo-to pentasialo-transferrin isoforms were separated in 16 min.…”
Section: Proteins In Bloodmentioning
confidence: 99%
“…Most capillary electrophoretic methods are based on a zone electrophoretic separation in dynamically coated capillaries (e.g., with diaminobutane, spermine, diethylenetriamine, etc.) with direct UV detection at 200-214 nm wavelengths of the separated zones [128][129][130][131]. Quite recently, Wuyts et al [132] reported a CZE method using proprietary reagents (CEofix ® CDT buffer system, Analis, Namur, Belgium) that provide a dynamic double coating of the capillary based on polycation and polyanion.…”
Section: Analysis Of Carbohydrate-deficient Transferrin (Cdt)mentioning
confidence: 99%